Utilização do brinquedo terapêutico na assistência à criança hospitalizada - Fontes, Cassiana Mendes Bertoncello [UNESP]; Mondini, Cleide Carolina da Silva Demoro; Moraes, Márcia Cristina Almendros Fernandes; Bachega, Maria Irene [UNESP]; Maximino, Natália Patrisi (FapUNIFESP (SciELO), 2010)
This is an exploratory and descriptive study that was jointly carried out by Nursing Care and Occupational Therapy as part of a Research Project that intended to prepare children for elective surgery at the University of São Paulo's Hospital de Reabilitação de Anomalias Craniofaciais. Objective: using toys as a therapeutic resource for relieving the child's real and unconscious tensions concerning hospitalization for surgical treatment at the HRAC - USP. Method: 44 children participated in the study. An observation form was used to collect data and it was applied at two separate times: the first time was the day before the surgery was to take place and the second on the day of the surgery just before the event. Twenty one variables were elaborated by the researchers to categorize behaviors regarding hospitalization. The resources used were: storytelling, dramatization and demonstration of nursing interventions with puppets dressed in surgical garb (gloves, surgical gown, mask and cap) with medical equipment commonly used in hospital. Results: of the 21 variables analyzed, 8 showed statistically significant differences on the McNemar Test (p<0.05). Conclusion: interactive play enables hospitalized children to interact in the hospital environment, so that they can express feelings and emotions and it contributes to humanized hospital assistance.
Using therapeutic toys in care with hospitalized children
Keywords: Child Behavior; Hospitalized Children; Occupational Therapy; Special Education; Toy Therapy